Pengaruh Blended Learning Berbasis Flipped Classroom Pada Mata Pelajaran Prakarya Terhadap Hasil Belajar Siswa Kelas X SMK - Wiratama Darmawan; Dedi Kuswandi; Henry Praherdhiono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
The purpose of this study was to examine the effect of blended learning based flipped classroom on study prakarya to class X learning outcomes of Ma'arif Batu Vocational School. The type of research used is quasi-experimental with non-random group selection (Pre-test - Post-test Control Group Design) (Sugiyono, 2014). The data collection technique used is a test technique. The pre-test is done to retrieve a student's initial ability data, while the post-test is conducted to test the effect of treatment. In this study, three statistical tests will be carried out namely, (1) normality test, (2) homogeneity test, (3) hypothesis test. Thus the hypotheses that have been formulated can be proven, namely, H0 is rejected and H1 is accepted because the significance value is 0,000 <0.05 at a significance level of 5% so that it can be concluded that There is an influence of blipped learning based on Flipped Classroom on the subjects of the Prakarya to learning outcomes of Grade X students of the Ma'arif Vocational School.